Effects of warming and nitrogen deposition on the coupling mechanism between soil nitrogen and phosphorus in Songnen Meadow Steppe, northeastern China - Zhang, Nanyi; Guo, Rui; Song, Piao; Guo, Jixun; Gao, Yingzhi (Soil biology & biochemistry, 2013)
Songnen Meadow Steppe, which is in northeast China, is increasingly affected by global warming and incremental increases in atmospheric nitrogen deposition. However, the responses of nitrogen (N) and phosphorus (P) in steppe soil, and of the coupling mechanism between them, to the dual effects of global warming and N deposition are still unknown. In this study, the effects of simulated atmospheric warming and N deposition on N and P in Songnen steppe soil, as well as on the coupling between N and P, were examined under in situ conditions. Infrared heaters were used to elevate soil temperature by approximately 1.7 °C since 2006. N additions were treated once a year with aqueous ammonium nitrate at a rate of 10 g m−2 a−1. During the four-year study, addition of N increased the amount of total N, and available N, as well as the rate of N mineralization in the soil. Moreover, the amounts of total P and available P in the soil were considerably reduced. Thus, the N:P ratio increased, and the coupling between N and P decreased. Similar values for the N:P ratio were obtained for the addition of N by itself and for the combination of warming and addition of N, which indicates that a small amount of soil warming in Songnen Meadow Steppe would not have a substantial effect on the ratio. With the growth of China's industrialization, N deposition continues to increase. The study area of Songnen Meadow Steppe, and northeast China in general, are characterized by widespread distribution of saline alkali soil. Therefore, the finding of increased P limitation in the soil of Songnen Meadow Steppe has major implications for ecosystems in northeast China. Reasonable regulation and management of meadow soil nutrients will be of great importance in increasing soil productivity and promoting sustainable use of grassland ecosystems.